Repigmentation in vitiligo: position paper of the Vitiligo Global Issues Consensus Conference. (January 2017) - Gan, Emily Y.; Eleftheriadou, Viktoria; Esmat, Samia; Hamzavi, Iltefat; Passeron, Thierry; Böhm, Markus; Anbar, Tag; Goh, Boon Kee; Lan, Cheng‐Che E.; Lui, Harvey; Ramam, M.; Raboobee, Noufal; et al.
Summary: The Vitiligo Global Issues Consensus Conference (VGICC), through an international e‐Delphi consensus, concluded that 'repigmentation' and 'maintenance of gained repigmentation' are essential core outcome measures in future vitiligo trials. This VGICC position paper addresses these core topics in two sections and includes an atlas depicting vitiligo repigmentation patterns and color match. The first section delineates mechanisms and characteristics of vitiligo repigmentation, and the second section summarizes the outcomes of international meeting discussions and two e‐surveys on vitiligo repigmentation, which had been carried out over 3 yr. Treatment is defined as successful if repigmentation exceeds 80% and at least 80% of the gained repigmentation is maintained for over 6 months. No agreement was found on the best outcome measure for assessing target or global repigmentation, therefore highlighting the limitations of e‐surveys in addressing clinical measurements. Until there is a clear consensus, existing tools should be selected according to the specific needs of each study. A workshop will be conducted to address the remaining issues so as to achieve a consensus.